العلامة ابن سحمان وعلاقته بالدعوة النجدية: The Scholar Ibn Sahman and his Relationship to the Najd Call (Khairulummah, 2022)
AbstractArticle Topic: Ibn Sahman and His relations witg Dawah in the Najd Region.Origins: It is extracted from Doctorate Thesis by researcher named Dr. Abdur Rahman s/o Shamsud Din under the Supervision of Professor Dr. Badr bin Muqbil Al-Zufairi.Subject: It discusses the life of Allama Sulaiman Bin Sahman and His relation with the ‘Dawah’ Struggle that initiated in Al-Najd Region under watchful eyes of its founder Imam Muhammad Bin Abdul Wahab Bin Sulaiman Al-Tamimi (d: 1206H).Composition of the Research: Research is composed of an Introduction in addition to two Chapters and ending. Moreover the first Chapter includes biography of Ibn Sahman while the second Chapter explains Ibn Sahman’s bond with ‘Dawaah’ in Al-Najd Region. The ending has essential Objectives obtained from the Research.
Keywords: Ibn-Sahman, ‘Dawah in Al-Najd Region and Sulaiman Bin Sahman.